Critical Synthesis Package: 2-Item Depression Screener - Maria van Zuilen (Association of American Medical Colleges, 2014)
Abstract This Critical Synthesis Package contains: (1) a Critical Analysis of the psychometric properties and application to health sciences education for the 2-Item Depression Screener, and (2) a copy of the 2-Item Depression Screener instrument developed by Mary Whooley, MD. The 2-Item Depression Screener is a brief depression screen initially designed for the primary care setting. It has since been used with a range of patient populations. It assesses depressed mood and anhedonia by asking the patient: "During the past month, have you often been bothered by (1) feeling down, depressed, or hopeless and (2) little interest or pleasure in doing things?" A "Yes" answer to either question is considered a positive screen. Data on the diagnostic validity of the 2-Item Depression Screener comes from studies with multiple patient populations. Sensitivity of the screener is high and compares favorably to that of longer measures. Specificity is somewhat lower than longer measures. Hence, a positive screen must be followed up by further evaluation to determine if the patient meets diagnostic criteria for a mood disorder. A negative screen on the other hand makes it highly unlikely the patient is depressed. Given its brevity and ease of implementation as either a clinician-administered or self-report tool, it has clear utility in a busy clinical setting. Use of the 2-Item Depression Screener has been shown to have an effect on case finding and on the initiation of antidepressant treatment; however, there are no studies linking depression screening to improved outcomes. While the 2-Item Depression Screener has been well-studied with patient populations, there is little research on its use with health care trainees. The applicability of this measure to health sciences education deserves additional investigation.